PWE-092 Systemic tpa for acute splanchnic vein thrombosis. (22nd June 2015) - Patch, D; Marshall, A; O'Beirne, J; Chowdary, P; Sekhar, M; Westbrook, R; Thorburn, D; Davidson, B; Yu, D
Abstract : Introduction: Acute portal mesenteric vein thrombosis, when extensive, is associated with catastrophic complications of gut infarction, short bowel syndrome, PN dependence and death. The absence of a satisfactory therapeutic regimen has prompted the recommendation for alternative therapies (Hepatology 2010;51:210–218). Based on the safety profile of prolonged low dose tPA in children with extensive deep vein thrombosis, we have developed a ward-based TPA protocol to be used in patients with acute splanchnic vein thrombosis and symptoms/radiological signs of gut ischaemia. This treatment algorithm was approved by RFH DTC. Method: Alteplase is commenced at a dose of 0.05 mg/kg/hr in patients with acute splanchnic vein thrombosis, after informed consent and an MDT decision involving surgery/radiology/hepatology. The standard contraindications to tPA apply. Monitoring involves 12 hrly FBC, clotting, fibrinogen. Thromboelastography/ROTEM were included as exploratory investigations. t-PA may be continued for 72 h. Contrast enhanced CT is performed at 48 h, or earlier if clinically indicated. TIPS is indicated if thrombus/symptoms persist at 72 h. Results: To-date, 6 patients have been treated with this regimen. Aetiology of thrombosis was Chiari malformation (1) previously undiagnosed JAK2+ve MPD (2) local sepsis (1) and unknown (2) (see Table 1 ). Three patients had complete radiologic normalisation of their splanchnic circulation, 2 of whom also required TIPS due to persistent PVT. Two patients re-permeated their SMV with complete resolution of clinical symptoms and radiological signs of gut ischaemia, but with persistent PV thrombus. One patient did not have a radiological response, although their pain resolved. No patient required surgery for gut ischaemia. All patients survived and were discharged with normal enteric function. Two patients had their infusion interrupted; one for an arterial line puncture site bleed, and one for worsening gut symptoms (infusion re-started). Conclusion: This early experience suggests that systemic tPA in patients with acute PMVT and symptoms/signs of gut ischaemia can be used to achieve resolution of thrombus and symptoms and avoid catastrophic complications of gut infarction. We propose that tPA is of value in a multi-modality approach to the management of acute splanchnic vein thrombosis. Disclosure of interest: None Declared.